Rethinking community sanctions : social justice and penal control - Stubbs, Julie; Russell, Sophie; Baldry, Eileen; Brown, David; Cunneen, Chris; Schwartz, Melanie (Emerald Publishing Limited, 2023)
Rethinking Community Sanctions: Social Justice and Penal Control redresses the invisibility of community sanctions in a popular imaginary dominated by the prison, resulting in their being seen as not prison, not punishment, a let off, or expression of mercy. Based on insights from interviews with key participants in 3 Australian jurisdictions, case studies of selected programmes and policies, and the international literature, the authors focus on the effects of community sanctions among groups vulnerable to penal control: First Nations peoples, women, and those with disabilities, along with those at the intersections of these groups. Arguing that developing a better, more democratic politics around community sanctions requires coming to terms with the wider carceral web in which vulnerable groups are ensnared, they demonstrate the importance of connecting criminal legal system struggles with broader movements for community control, self-determination, and sovereignty.